A consistent approach for processing and interpretation of data from concrete bridge members collected with a hand-held GPR device. (1st July 2015) - Clem, Daniel J.; Schumacher, Thomas; Deshon, Jordan P.
Highlights: We present a consistent approach for processing and interpretation of GPR data. Data was collected using a comparatively inexpensive hand-held GPR device. Five data processing steps are proposed using an exact signal travel path. Cross-correlation is used to detect and distinguish the type of reflector. Our approach was evaluated on mock-up concrete bridge members in the laboratory. Abstract: Non-destructive testing (NDT) techniques have become important means to inspect concrete bridge members. In particular, ground penetrating radar (GPR) has the ability to provide valuable information with respect to geometry and location of reinforcing bars, and, in some cases, areas of deterioration such as corrosion or potential delaminations. In this paper, we present a consistent methodology to process and interpret data from a hand-held GPR device. These small devices are often used by practitioners to more accurately inspect areas of interest while traffic control is maintained. Our methodology uses an exact non-linear time-depth relationship and cross-correlation to locate and visualize reflectors. The polarity and amplitude of the reflected pulse is also extracted and gives further information on the type of reflector, e.g., air vs. steel. Data collected and processed from three laboratory mock-up specimens are presented and discussed, and further work is proposed.